Implementation of the MATRIX Staffing Grid Improves Nurse Satisfaction With Rehabilitation Unit Staffing. Issue 4 (10th August 2021) - Riley, Yahaddy; Stitt, Jacqueline; Hill, Cynthia M.; Stutzman, Sonja E.; Venkatachalam, Aardhra M.; Aguilera, Veronica; Ifejika, Nneka L.
Abstract : Supplemental digital content is available in the text. ABSTRACT: BACKGROUND: Information on nurse satisfaction and unit acuity is scarce in the literature. The purpose of this study is to evaluate the effect of the MATRIX Staffing Grid (MSG) on nurse assignment satisfaction in a 20-bed inpatient rehabilitation facility. METHODS: Prospective systematic implementation study of the MSG occurred in 5 phases: development, baseline, run-in, implementation, and sustainability. Pretest/posttest nursing satisfaction data were analyzed using Wilcoxon-Mann-Whitney tests. RESULTS: Analysis of 128 satisfaction surveys demonstrated that the median total satisfaction score increased by 35% after MSG implementation ( P < .05), with no change in patient satisfaction or adverse event rates. CONCLUSION: A systematic approach to implementation of the MSG evidence-based practice significantly improved nursing satisfaction with patient assignment in a way that addressed specific needs. The MSG has now been adopted into practice at our institution. The MSG may be feasible for implementation in inpatient rehabilitation units to improve staffing satisfaction.